2017
DOI: 10.5812/ogcr.8953
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vaginal pH on the Efficacy of Vaginal Misoprostol for the Induction of Midtrimester Pregnancy Termination

Abstract: Background: Vaginal misoprostol is said to dissolve better in an acidic environment, thus, in this study we aimed to evaluate the influence of increasing vaginal acidity on the effectiveness of vaginal misoprostol for the induction of midtrimester pregnancy using acidic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, conflicting results have been obtained in studies that the researcher's hypothesis was prostaglandins are effective in acidic media. Some studies have reported that acidic vaginal pH in the first and second trimesters has no effect on the induction of labor with Misoprostol, 14,19 while Rashwan et al reported positive and effective results 12 . According to the results of indirect studies, it is not yet possible to make an accurate conclusion about the effect of pH on the induction of the labor process.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, conflicting results have been obtained in studies that the researcher's hypothesis was prostaglandins are effective in acidic media. Some studies have reported that acidic vaginal pH in the first and second trimesters has no effect on the induction of labor with Misoprostol, 14,19 while Rashwan et al reported positive and effective results 12 . According to the results of indirect studies, it is not yet possible to make an accurate conclusion about the effect of pH on the induction of the labor process.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13]18 Other studies suggest that when the acidic environment in the vagina is created with acetic acid, the success rate of Misoprostol increases 12,13 and some studies have considered the effectiveness of vaginal Misoprostol in moderate acidity 5 and refused the effect of acidic environment. 14 of prostaglandins, reducing the active phase of labor. 15,16 Finally, Chandra et al have reported no efficacy and the optimal pH for achieving maximal Misoprostol efficacy has not yet been identified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations